2019
DOI: 10.35974/isc.v7i1.905
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Academic Dishonesty and Procedural Justice among University Students in Thailand

Abstract: This study investigate the relationship between students‟ perception of procedural justice andacademic dishonesty among students at a Thai university. A cross-sectional survey designwas employed that utilized a correlational analysis. The sample size derived from theuniversity consisted of 133 respondents. Results indicated that there were no difference in thestudents‟ perception between procedural justice and academic dishonesty when compared bygender, program, class, or faculty. A weak positive relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite the demonstrated correlation between fairness and cheating, there are still gaps in the prior studies' findings. Some researchers discovered a positive significant correlation between fairness and dishonesty (Kaufmann and Tatum, 2018;Nigjeh et al, 2019;Münscher et al, 2020;Münscher, 2022), whereas other studies demonstrated a weak positive relationship (Akbas lı et al, 2019;Phutikettrkit and Thomas, 2019). Recognizing the disparity, we attempted to bridge the gap by proposing spirituality as a moderating variable.…”
Section: Spirituality and Online Cheatingmentioning
confidence: 98%
See 4 more Smart Citations
“…Despite the demonstrated correlation between fairness and cheating, there are still gaps in the prior studies' findings. Some researchers discovered a positive significant correlation between fairness and dishonesty (Kaufmann and Tatum, 2018;Nigjeh et al, 2019;Münscher et al, 2020;Münscher, 2022), whereas other studies demonstrated a weak positive relationship (Akbas lı et al, 2019;Phutikettrkit and Thomas, 2019). Recognizing the disparity, we attempted to bridge the gap by proposing spirituality as a moderating variable.…”
Section: Spirituality and Online Cheatingmentioning
confidence: 98%
“…Similarly, lecturers will attempt to construct their self-image in accordance with their duties and responsibilities as educators. Even if the treatment is adverse, lecturers who are consistent in their treatment of students will be viewed as more fair than lecturers whose behavior is more inconsistent (Phutikettrkit and Thomas, 2019). Students at the university level are frequently concerned with procedural fairness, indicating that they believe lecturers are sometimes unjust (Horan et al, 2010).…”
Section: Perceived Lecturer Justice and Online Cheatingmentioning
confidence: 99%
See 3 more Smart Citations